Dataset risk perception scale healthcare professionals. - Badía-Gómez, María Carmen; Alarcón-Postigo, Rafael; Trillo-Legaz, Javier; Miranda-Páez, Jesús (Universidad de Málaga, 2024)
Risk perception is a cognitive process that relies on each person's information, about different issues such as contexts, other people, objects, and which is processed immediately, organising a judgement or value that will condition their behaviour. The aim of this study is to carry out an exhaustive analysis of the psychometric properties of the COVID-19 Pandemic Risk Perception Scale (PRPS). The sample was 405 healthcare professionals ranged between 22 and 65 years, belonging to the hospital emergency services and the critical care unit in southern Spain. A descriptive cross-sectional study was carried out. In order to obtain evidence of validity based on the internal structure of PRPS, we conducted a confirmatory factor analysis (CFA). A reliability analysis was performed, calculating the McDonald’s omega coefficient (ω), and an item analysis was also performed, calculating the corrected item-total correlation coefficient. Finally, evidence of validity based on the relationship with other variables was obtained. The results of the CFA supported a unidimensional structure of the PRPS. The reliability of the test scores was .95. Evidence of validity was provided by a positive correlation between the PRPS score and the Patient Health Questionnaire (PHQ-9), and by a negative correlation between the PRPS score and the reduced version of the Spanish adaptation of the Psychological Well-Being Scale (PWBS). The results indicate that the Pandemic Risk Perception Scale (PRPS) has shown adequate psychometric properties, which makes it a useful instrument in the context of health professionals, postulated as an easy and brief tool to complete.
Keywords: Psicometría; Personal sanitario; Psicología; Servicios de salud; Evaluación del riesgo; Risk perception; Healthcare professionals; Confirmatory factor analysis; Evidence of validity